2010
DOI: 10.1534/genetics.110.116756
|View full text |Cite
|
Sign up to set email alerts
|

Gene Duplication, Gene Conversion and the Evolution of the Y Chromosome

Abstract: Nonrecombining chromosomes, such as the Y, are expected to degenerate over time due to reduced efficacy of natural selection compared to chromosomes that recombine. However, gene duplication, coupled with gene conversion between duplicate pairs, can potentially counteract forces of evolutionary decay that accompany asexual reproduction. Using a combination of analytical and computer simulation methods, we explicitly show that, although gene conversion has little impact on the probability that duplicates become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 48 publications
2
56
0
Order By: Relevance
“…This may allow the restoration of a mutation-free gene copy at a locus with a deleterious mutation (depicted in red) through a gene conversion with another copy of the same gene family, and has been shown to oppose Y degeneration by analytical and computer simulation methods 109,110 . A consequence of gene conversion between the arms of a palindrome is a high amount of sequence identity between repeat units.…”
Section: Primate Y Chromosome As Revealed From Genomic Studiesmentioning
confidence: 99%
“…This may allow the restoration of a mutation-free gene copy at a locus with a deleterious mutation (depicted in red) through a gene conversion with another copy of the same gene family, and has been shown to oppose Y degeneration by analytical and computer simulation methods 109,110 . A consequence of gene conversion between the arms of a palindrome is a high amount of sequence identity between repeat units.…”
Section: Primate Y Chromosome As Revealed From Genomic Studiesmentioning
confidence: 99%
“…Recombination decouples such associations, and permits diploidy to evolve, despite the long-term fitness cost. Such interactions between ploidy and recombination have parallels in various other aspects of genome evolution, including the evolution of genomic imprinting [44], [68] and the establishment of gene duplicates [69], [70].…”
Section: Resultsmentioning
confidence: 99%
“…Also, gene duplication coupled with gene conversion between duplicates can potentially maintain gene function by counteracting evolutionary Y decay (Rozen et al 2003;Charlesworth 2003;Noordam and Repping 2006). A combination of analytical and computer simulation methods also showed that gene conversion effectively maintains the functionality of Y-linked duplicates that have already become fixed, although it has little impact on the probability that duplicates become fixed within a population (Connallon and Clark 2010). Therefore, the functions of T. muenninki Y-linked genes may have been maintained not only by translocation but also by amplification on the sex chromosomes fused to an autosomal pair.…”
Section: Discussionmentioning
confidence: 99%